Theoretical insights into the effect of solvents on the [4 + 2] cycloaddition of singlet oxygen to substituted anthracenes: A change from a stepwise process to a concerted process. (6th March 2019) - Fudickar, Werner; Linker, Torsten
Abstract: The [4 + 2] cycloadditions of singlet oxygen to 9, 10‐diphenylanthracene (1 ) and the meta and para isomers of 9, 10‐dipyridylanthracene (2 m / p ) and 9, 10‐methoxyphenylanthracene (3 m / p ) have been studied by density functional calculations in the gas phase at the UB3LYP/6‐31G * level and for the first time in solvents at the conductor‐like polarizable continuum model (CPCM) UM062X/6‐31G * level. The differences in calculated transition state (TS) energies derived from this method are in line with experimentally observed reactivity orders in solution. For the gas‐phase reaction, the first TS of the stepwise pathway (TS1 ) has biradical character, and its energy lies below the energy of the TS of the concerted path (TS conc ). In contrast, in the solvent acetonitrile, TS1 resembles a zwitterion and lies significantly higher than theTS conc . Thus, a concerted mechanism applies in solvents, and the energy gap between the TS of the two processes decreases with decreasing polarity. A change from a pyridyl against a methoxyphenyl substituent in the para position causes a maximal reduction of the activation barrier by approximately 1.7 kcal/mol, resulting in a fivefold increased reactivity. Abstract : The reactivity of anthracenes with 1 O2 is controlled by the substituents at the 9, 10 position and the polarity of the solvent. DFT calculations of the transition states during the photooxygenation reveal a concerted reaction mechanism with a good correlation between TS energies and reactivity orders.